A hidden Markov model to characterise motivation level in MOOCs learning. (22nd September 2020) - Chen, Yuan; Han, Dongmei; Xia, Lihua
The effect of MOOCs learning is closely related to the learning ability of learners. In order to study the change of learners' learning ability, this paper uses hidden Markov model to analyse the continuous learning process of MOOCs learners. Based on the data of learning platform of www.shlll.net, the model is established. The empirical results show that the distinction between learners' high and low learning ability is more obvious. Based on the above findings, this paper further analyses the learning behaviour differences of participants in learning activities and continuous learning. The method proposed in this paper provides a new way for the study of MOOCs learning, which is helpful for the development of MOOCs learning.